A Study on Factors Causing Loss of Interest in Mathematics Among High School Students In Thiruvallur District - Moses, Belbha (International Journal of Advanced Research in Peace, Harmony and Education, 2023)
Anxiety or fear related to math issues is known as math anxiety. It is a method of characterizing anxiety that happens in a particular situation rather than a specific medical condition. A person with math anxiety could experience anxiety whenever they need to apply their mathematical abilities, from schoolwork to figuring out how much their meal will cost. Some people may only experience it when they are unable to use a calculator or write down information. Others might experience it even though they have access to these resources. All facets of human life are impacted by mathematics on various levels. According to studies, mathematics is a science of size and number that is extremely helpful almost everywhere. This is due to the fact that it is necessary for problem solving and outcome prediction across all academic disciplines. Any person or nation must be capable of understanding mathematics in order to engage in domestic and international business, make scientific discoveries, develop new technologies, solve problems, and make decisions in a variety of real-world scenarios. Consequently, the title of the current investigation is “A study on factors causing loss of interest in mathematics among high school students in Thiruvallur District.